Analysis Of Job Crafting and Organizational Support on Employee’s Innovative Work Behavior with Work Engagement as An Intervening Variable - Dahlan, Nurlaila; Mardiana, Ria; Reni, Andi (SEIKO : Journal of Management & Business, 2023)
Employees play a significant part in determining the fate of a company. Employees are anticipated to retain innovative actions for the effectiveness and sustainability of a company. One of the factors that can impact Employees innovative work behavior is through job crafting, which refers to the tone- initiated changes made by workers to balance job demands and coffers. This, in turn, affects the position of organizational or company success in achieving its pretensions. Organizational support plays a pivotal part in enhancing Employees provocation to develop their capabilities. Employees innovative behavior can also be enhanced through work engagement, which is a concept where employees have a high commitment and enthusiasm for their work. This study aims to examine the influence of job crafting and organizational support on Employees innovative behavior with work engagement as the interceding variable. The exploration system used is quantitative descriptive system. The repliers in this study were 77 workers of PT. Infomedia Nusantara. Data collection ways used questionnaires, and data analysis ways used Partial Least Forecourt (SmartPls). The results of the study showed that organizational support had a significant positive effect on work engagement as a mediator. Job crafting was proven to have a significant and positive effect on workers' innovative behavior. Job crafting also had a positive and significant effect on work engagement as a mediator. Work engagement as a mediator had a positive and significant effect on innovative behavior. Keywords: job crafting, organizational support, work engagement, innovative behavior